2020
DOI: 10.1017/s1751731120000622
|View full text |Cite
|
Sign up to set email alerts
|

Energy and protein requirements of Holstein × Gyr crossbred heifers

Abstract: Nutrient requirements in cattle are dependent on physiological stage, breed and environmental conditions. In Holstein × Gyr crossbred dairy heifers, the lack of data remains a limiting factor for estimating energy and protein requirements. Thus, we aimed to estimate the energy and protein requirements of Holstein × Gyr crossbred heifers raised under tropical conditions. Twenty-two crossbred (½ Holstein × ½ Gyr) heifers with an average initial BW of 102.2 ± 3.4 kg and 3 to 4 months of age were used. To estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…The overall k PG calculated (0.52 ± 0.0222) was close to the value reported to goats in AFRC ( 4 ) (0.59) but lower than that adopted by SCA ( 28 ) and NRC ( 1 ), in which both adopted 0.70. This value was also close to that of recent studies in dairy cows by Castro et al ( 29 ) of 0.51. Because the differences in protein content in tissue gain possibly affect this efficiency for growth ( 1 ), we would expect different values of k PG between sexes.…”
Section: Resultssupporting
confidence: 93%
“…The overall k PG calculated (0.52 ± 0.0222) was close to the value reported to goats in AFRC ( 4 ) (0.59) but lower than that adopted by SCA ( 28 ) and NRC ( 1 ), in which both adopted 0.70. This value was also close to that of recent studies in dairy cows by Castro et al ( 29 ) of 0.51. Because the differences in protein content in tissue gain possibly affect this efficiency for growth ( 1 ), we would expect different values of k PG between sexes.…”
Section: Resultssupporting
confidence: 93%
“…We used BW, SBW, and EBW for the comparisons previously described. For Jiao et al (2015) [95] and Moreira (2016) [86], we used SBW = 0.96 × BW [9] because in that study the NE m requirement values were expressed as BW 0.75 , but for Castro et al (2020) [96], we used EBW = 0.894 × SBW because the NE m requirement values were originally expressed as EBW 0.75 . Therefore, the low accuracy of predictions from the DMI model of NRC heifers could also be related to differences in NE m requirements and genetic variation in crossbred heifers.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study suggested that NE m requirements of heifers increased over time, similar to cows [ 94 ], and estimated as 122 kcal/kg of SBW 0.75 for Holstein heifers from 6 to 22 months of age [ 95 ]. For crossbred Holstein × Gyr heifers, the requirement of NE m is suggested to be between 104 kcal/kg of SBW 0.75 (17 months and 1 / 2 Holstein × 1 / 2 Gyr) [ 86 ] and 67 kcal/kg of SBW 0.75 (3 to 7 months and 1 / 2 Holstein × 1 / 2 Gyr) [ 96 ]. We used BW, SBW, and EBW for the comparisons previously described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The breed’s performance in Southeast Asian countries ranges from 1710 to 1978 kg of milk/lactation [ 36 , 54 ]. Another well-established breed is the Holstein × Gyr breed, where several requirement and feed efficiency studies have been conducted in recent years [ 55 , 56 , 57 ]. The breed was observed to produce an average milk yield of 5118 and 5211 kg/lactation of 1/2 and 7/8 Holstein composition, respectively [ 38 ].…”
Section: Temperate–tropical Crossbreeding Endeavors In Developing Countries In the Tropicsmentioning
confidence: 99%